1984
DOI: 10.1128/aem.47.4.780-787.1984
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Growth Modification by Compressed Gases and Hydrostatic Pressure

Abstract: Studies of the growth-modifying actions for Escherichia coli, Saccharomyces cerevisiae, and Tetrahymena thermophila of helium, nitrogen, argon, krypton, xenon, and nitrous oxide led to the conclusion that there are two definable classes of gases. Class 1 gases, including He, N2, and Ar, are not growth inhibitors; in fact, they can reverse the growth inhibitory action of hydrostatic pressures. Class 2 gases, including Kr, Xe, and N20, are potent growth inhibitors at low pressures. For example, at 24°C, 50% grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…The measurement of oxygen consumption by S. cerevisiae at elevated hydrostatic pressures illustrated the utility of this type of sensor. Previous studies have shown a decrease in growth rate in S. cerevisiae cultures at increased hydrostatic pressures (Thom and Marquis 1984;Marquis 1993). Because the optrode is insensitive to pressure fluctuations, it is possible to continuously monitor oxygen tension within the reaction chamber while simultaneously altering the hydrostatic pressure.…”
Section: Discussionmentioning
confidence: 94%
“…The measurement of oxygen consumption by S. cerevisiae at elevated hydrostatic pressures illustrated the utility of this type of sensor. Previous studies have shown a decrease in growth rate in S. cerevisiae cultures at increased hydrostatic pressures (Thom and Marquis 1984;Marquis 1993). Because the optrode is insensitive to pressure fluctuations, it is possible to continuously monitor oxygen tension within the reaction chamber while simultaneously altering the hydrostatic pressure.…”
Section: Discussionmentioning
confidence: 94%
“…2 an attempt was made to fit the experimental data to eq 40. With respect to the yeast cell under a high-pressure study, P,,, is known in the literature to be 19898.6 kPa gauge (=2842.4 psig) (Furui and Yamashita, 1983;Kitano and Ise, 1988;Taylor and Jannasch, 1976;Miller et al, 1988;Thibault et al, 1987;Thom and Marquis, 1984;Zo-bel and Budge, 1965). By using the above P,, and applying a regression analysis, the constants a and / 3 were found to be 0.25 and 0.775.…”
Section: Resultsmentioning
confidence: 99%
“…Influence of gaseous environment and E h on yeast growth was reported previously in the literature. However, Thom and Marquis (1984) showed that hydrogen and helium gases used for compression of culture were not growth inhibitory for S. cerevisiae. Influence of gas and ⁄ or E h on yeast growth could be dependent on yeast strain and ⁄ or medium culture.…”
Section: Discussionmentioning
confidence: 99%